Efeito da sertralina e de sua associação com insulina em ratos portadores de diabetes mellitus tipo 2 induzidos por estreptozotocina submetidos ao teste do nado forçado - Sestile, Caio César (2015)
The type 2 diabetes mellitus (DM2) and depression disorder (DD) are chronic diseases of high prevalence in the world. It is estimated that 11% to 30% of patients with DM2 have DD. The chronic condition of DM2 may be influencing the mood of individuals making them susceptible to the development of DD. Some studies suggest that insulin-serotonin system of the central nervous system (CNS) may be responsible for the development of psychiatric diseases associated with metabolic diseases. The aim of this study was to evaluate the antidepressant-like activity of chronic treatment with sertraline compared to treatment with insulin and the insulin-sertraline combination in Wistar rats with DM2 treated with streptozotocin (STZ), submitted to forced swimming test (FST). To this end, neonatal mice were treated with STZ (160 mg/kg, i.p.). After seven weeks was started treatment with sertraline (10 mg/kg, i.p.) and/or insulin (1UI or 2UI/kg, i.p.) for 21 days and the animals were submitted to the FST. The rats treated with STZ showed DM2 with glucose intolerance, after the experimental period proving the efficiency of induction by STZ. Animals with DM2 treated with sertraline showed less weight gain when compared to other groups and treatments. Chronic treatment with sertraline showed significantly reduced immobility time indicating antidepressant-like activity in non-diabetes rats and rats with DM2. Similarly, treatment with insulin or its combination with sertraline showed antidepressant-like activity in diabetic animals submitted to FST. However, it was not observed a significant reduction in immobility time in combined treatment compared to treatment alone. These results show that sertraline showed antidepressant-like activity in FST with significant weight loss in animals with DM2. Insulin also showed antidepressant-like activity. The combined treatment with insulin and sertraline showed no advantage over the treatments alone.